A review of the putative causal mechanisms associated with lower macular pigment in diabetes mellitus. Issue 2 (14th August 2019) - Scanlon, Grainne; Loughman, James; Farrell, Donal; McCartney, Daniel
Abstract: Macular pigment (MP) confers potent antioxidant and anti-inflammatory effects at the macula, and may therefore protect retinal tissue from the oxidative stress and inflammation associated with ocular disease and ageing. There is a body of evidence implicating oxidative damage and inflammation as underlying pathological processes in diabetic retinopathy. MP has therefore become a focus of research in diabetes, with recent evidence suggesting that individuals with diabetes, particularly type 2 diabetes, have lower MP relative to healthy controls. The present review explores the currently available evidence to illuminate the metabolic perturbations that may possibly be involved in MP's depletion. Metabolic co-morbidities commonly associated with type 2 diabetes, such as overweight/obesity, dyslipidaemia, hyperglycaemia and insulin resistance, may have related and independent relationships with MP. Increased adiposity and dyslipidaemia may adversely affect MP by compromising the availability, transport and assimilation of these dietary carotenoids in the retina. Furthermore, carotenoid intake may be compromised by the dietary deficiencies characteristic of type 2 diabetes, thereby further compromising redox homeostasis. Candidate causal mechanisms to explain the lower MP levels reported in diabetes include increased oxidative stress, inflammation, hyperglycaemia, insulin resistance, overweight/obesity and dyslipidaemia; factors that may negatively affect redox status, and the availability, transport and stabilisation of carotenoids in the retina. Further study in diabetic populations is warranted to fully elucidate these relationships.